Harnessing the gut microbiome: a potential biomarker for wild animal welfare - Sonnega, Sam; Sheriff, Michael J. (Frontiers in Veterinary Science, 2024)
The welfare of wild animal populations is critically important to conservation, with profound implications for ecosystem health, biodiversity, and zoonotic disease transmission. Animal welfare is typically defined as the accumulated affective mental state of an animal over a particular time period. However, the assessment of animal welfare in the wild poses unique challenges, primarily due to the lack of universally applicable biomarkers. This perspective explores the potential role of the gut microbiome, a dynamic and non-invasive biomarker, as a novel avenue for evaluating animal welfare in wild animals. The gut microbiome, through interactions with the host’s physiology, behavior, and cognition, offers a promising opportunity to gain insights into the well-being of animals. In this synthesis, we discuss the distinction between fitness and welfare, the complexities of assessing welfare in wild populations, and the linkages between the gut microbiome and aspects of animal welfare such as behavior and cognition. We lastly elucidate how the gut microbiome could serve as a valuable tool for wildlife managers, with the potential to serve as a non-invasive yet informative window into the welfare of wild animals. As this nascent field evolves, it presents unique opportunities to enhance our understanding of the well-being of wild animals and to contribute to the preservation of ecosystems, biodiversity, and human health.